Synthesis, Properties and Potential Applications of Porous Graphene: A Review - Russo, Paola; Hu, Anming; Compagnini, Giuseppe (Nano-Micro Letters, 2013)
Since the discovery of graphene, many efforts have been done to modify the graphene structure for integrating this novel material to nanoelectronics, fuel cells, energy storage devices and in many other applications. This leads to the production of different types of graphene-based materials, which possess properties different from those of pure graphene. Porous graphene is an example of this type of materials. It can be considered as a graphene sheet with some holes/pores within the atomic plane. Due to its spongy structure, porous graphene can have potential applications as membranes for molecular sieving, energy storage components and in nanoelectronics. In this review, we present the recent progress in the synthesis of porous graphene. The properties and the potential applications of this new material are also discussed.